Experimental study on the radiative heat transfer in a multi-hole porous radiant burner with internal combustion regime. (25th January 2022) - Vahidhosseini, Seyed Mohammad; Esfahani, Javad Abolfazli; Kim, Kyung Chun
Graphical abstract: Highlights: The effect of internal zone's height on the radiant efficiency of internal regime. An increment of 13.1% in radiant efficiency compared to a multi-layer PRB. A new radiative heat transfer based non-dimensional number is defined. The radiative non-dimensional number is only a function of geometry, not power. The maximum radiant efficiency is occurred at the equivalence ratio of 0.9. Abstract: An experimental study was performed on the radiative heat transfer in a porous radiant burner (PRB) with an internal combustion regime (ICR). A multi-hole plate and a high pore density SiC porous foam were used to form the jet-shaped flames and the ICR, respectively. For local temperature measurement, a movable Cartesian mechanism is used for the thermocouple. The effects of three independent parameters of input power, P, equivalence ratio, ϕ, and the distance between the multi-hole plate and porous medium (PM), d, on radiative surface temperature and radiant efficiency are investigated. The results show that the radiant efficiency increases 13.1% compared to a multi-layer PRB in the literature at the same firing rate. In addition, the maximum radiant efficiency for all operating conditions occurred at ϕ = 0.9 . Moreover, the radiative surface temperature decreases, a decrease of 2.25%, by increasing d from 85 mm to 145 mm at P, ϕ = 8.25 k W, 0.9 . However, the radiative heat transfer of the PM, as well as the radiant efficiency, does not decrease sharply due to the view factor increment by increasing d . Furthermore, it was concluded that a new non-dimensional number, related to the radiative heat transfer, can be defined by dividing the radiative heat transfer to the burner's outside to the radiative heat transfer to the burner's side walls. This heat transfer based non-dimensional number is only a function of d, and it behaves like an ascending function that is independent of input power.